Competitive Advantage Strategies for the Success of SMEs in the School of Entrepreneurship Bina Amanah Cordova - Wijaya, Richy; Darasih, Ratna; Takaya, Rowlan; Lutfi, M. Yudhi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy. However, many MSME entrepreneurs lack sufficient understanding of competitive advantage strategies, making it difficult for them to sustain and grow their businesses. This study aims to provide training on competitive advantage strategies for MSME entrepreneurs at the Bina Amanah Cordova Entrepreneurship School (SKBAC). The training was conducted in collaboration with the Faculty of Economics and Business, Universitas Trisakti, through a community service program. The research method involved counseling, experience sharing, and interactive discussions. The results showed an increased awareness and understanding among MSME entrepreneurs regarding differentiation, leadership, and responsiveness. Participants demonstrated improved knowledge and a higher likelihood of implementing competitive advantage strategies in their businesses. This program highlights the importance of continuous education and mentoring to ensure the long-term success of MSMEs.